The anti‐mitotic agents PTC‐028 and PTC596 display potent activity in pre‐clinical models of multiple myeloma but challenge the role of BMI‐1 as an essential tumour gene. (30th March 2020) - Bolomsky, Arnold; Muller, Joséphine; Stangelberger, Kathrin; Lejeune, Margaux; Duray, Elodie; Breid, Helene; Vrancken, Louise; Pfeiffer, Christina; Hübl, Wolfgang; Willheim, Martin; Weetall, Marla; Branstrom, Art; et al.
Summary: Future progress in the treatment of multiple myeloma (MM) requires both the characterisation of key drivers of the disease and novel, innovative approaches to tackle these vulnerabilities. The present study focussed on the pre‐clinical evaluation of a novel drug class, BMI‐1 modulators, in MM. We demonstrate potent activity of PTC‐028 and PTC596 in a comprehensive set of in vitro and in vivo models, including models of drug resistance and stromal support. Treatment of MM cells with PTC‐028 and PTC596 downregulated BMI‐1 protein levels, which was found to correlate with drug activity. Surprisingly, BMI‐1 was dispensable for the activity of BMI‐1 modulators and MM cell growth. Our data rather point to mitotic arrest accompanied by myeloid cell leukaemia‐1 (MCL‐1) loss as key anti‐MM mechanisms and reveal impaired MYC and AKT signalling activity due to BMI‐1 modulator treatment. Moreover, we observed a complete eradication of MM after PTC596 treatment in the 5TGM.1 in vivo model and define epigenetic compounds and B cell leukaemia/lymphoma 2 homology domain 3 (BH3) mimetics as promising combination partners. These results bring into question the postulated role of BMI‐1 as an essential MM gene and confirm BMI‐1 modulators as potent anti‐mitotic agents with encouraging pre‐clinical activity that supports their rapid translation into clinical trials.